Performance and yield predictions in double cross hybrids of tropical grain maize - Sujiprihati, Sriani; Saleh, Ghizan; Ali, Eltahir Siddig (Universiti Putra Malaysia Press, 2003)
The use of double cross hybrids in maize was suggested to overcome the problem of seed production related to single cross resulting from low vigor and yield associated with the inbred parents. Double cross hybrids were known to perform quite well under a wide range of environmental conditions. As a part of an ongoing grain maize improvement program at Universiti Putra Malaysia, the best performing inbred lines were selected and crossed to produce single crosses. These single crosses were further used to produce some double cross hybrids. In this study, the performance of ten selected double cross hybrids was evaluated at two environments in the research areas of Universiti Putra Malaysia. The predicted performance of these double cross hybrids was also compared with the actual, using the method based on the mean values of non.parental single crosses. The best performing double cross hybrids, DC-26 and DC-34 were found to have high yields at both environments as well as in the combined analysis. DC-26 and DC-34 gave mean grain yields of 6125.0 and 5917.8 kg/ha respectively, at Field 2, 5648.9 and 5676.2 kg/ha respectively, at Share Farm, and 5887.0 and 5797.0 kg/ha respectively, in the combined analysis. From the correlation analysis, the actual and the predicted performances of the double cross hybrids were found to be in good agreement at each location and locations combined (r = 0.38, 0.46 and 0.27, respectively, at Field 2, Share Farm and at the two locations combined), implying that the method used for yield predictions in the crosses was appropriate.